Evaluation and analysis of coronoplasty procedures- a retrospective study - MONISHA.K,; KAREEM, NASHRA; ARAVIND.S., (The journal of contemporary issues in business and government, 2020)
Coronoplasty is the mechanical elimination of occlusal supracontact that may be present during functional moments. It deals with selective grinding or reducing of occlusal areas with the purpose of influencing mechanical contact, primitive contacts. The aim of the present study was to evaluate and analyse the number of coronoplasty procedures done among patients and the quadrant in which coronoplasty procedure was most prevalent. This study was carried out in a one year period (June 2019 to April 2020) on 56 patients (33 male patients, 23 female patients) who reported to a Private hospital, Chennai. All available data was extracted from an electronic dental record where the patient's case sheet was reviewed and results were obtained through SPSS analysis. From the results obtained 54.7 % males and 45.3 % females had participated in the study. Among the study population, quadrant 3 (42.17 %) had the most number of patients with coronoplasty treatment.Coronoplasty procedures was highest in 31-50 years amongst other age groups and males who underwent coronoplasty were more prevalent compared to females. The study concludes that the number of coronoplasty procedures reported to the hospital where 83 and quadrant 3 had the most number of procedures performed but the study was not statistically significant. Hence to conclude, the results of the present study are useful for generating hypotheses for further research with larger sample size and long term follow ups in order to create awareness about the importance of occlusal adjustment procedures.